2016
DOI: 10.1016/j.solener.2016.10.024
|View full text |Cite
|
Sign up to set email alerts
|

A novel experimental method to study metal vapor condensation/oxidation: Mg in CO and CO2 at reduced pressures

Abstract: A novel method is presented to study magnesium metal vapor condensation/oxidation in CO and CO 2 atmosphere at reduced pressures. Mg(s) was evaporated and mixed with an equimolar amount of CO or CO 2 at 1000°C after which the gaseous mixture flowed through an air cooled tubular condenser. Measurements of the axial temperature profile, calculation of partial pressures and analysis of deposits within the condenser allowed for identification of deposition/condensation onset temperatures, supersaturation ratio and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Considering T pyro minus 200 K (Table 2), the maximum temperature reached in experiments 32 and 33 was close to 2000 K. The high Mg content obtained in these two experiments with adequate physico-chemical parameters and heat treatment proved that the reversion reaction during the experiments and the oxidation during the collection are weak. This is mainly due to low partial pressure of CO and CO 2 during the whole duration of the experiments (< 10 Pa and < 1 Pa respectively for PCO and PCO 2 ) [27]. Using an improved collection process of the powders (collection on all the metallic sections, better system to filter the particles…), higher metallic yields close to 65-70 m% could be obtained.…”
Section: Correlations Between Thermodynamics Reaction Mechanisms Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering T pyro minus 200 K (Table 2), the maximum temperature reached in experiments 32 and 33 was close to 2000 K. The high Mg content obtained in these two experiments with adequate physico-chemical parameters and heat treatment proved that the reversion reaction during the experiments and the oxidation during the collection are weak. This is mainly due to low partial pressure of CO and CO 2 during the whole duration of the experiments (< 10 Pa and < 1 Pa respectively for PCO and PCO 2 ) [27]. Using an improved collection process of the powders (collection on all the metallic sections, better system to filter the particles…), higher metallic yields close to 65-70 m% could be obtained.…”
Section: Correlations Between Thermodynamics Reaction Mechanisms Andmentioning
confidence: 99%
“…The Magsonic TM process used a Laval nozzle at temperature above 1970 K and at atmospheric pressure with reversion below 10%, which demonstrated the possibility to obtain high Mg yields [26]. Finally, it had been recently demonstrated that rapid oxidation of Mg (g) occurred in the presence of CO 2 and that it is necessary to have low CO and CO 2 partial pressures to obtain high metal yield [27] .…”
Section: Introductionmentioning
confidence: 99%
“…  (see Fig. 2) were estimated combining balance eqns (12), (14), and (16) for the O 2 -Ar sweep and eqns (13) and (15) for the CO 2 -Ar sweep as…”
Section: Consumption Of C and Net Generation Of Co Owingmentioning
confidence: 99%
“…This scenario would impose the equality of the extents of the reverse reactions (4) and (5), i.e.   4 5  * * , thereby making the Boudouard reaction only a step of the reverse overall reaction (1), as suggested by Hischier et al 15…”
Section: Sweep Gasmentioning
confidence: 99%
See 1 more Smart Citation